Big Bob and the Halloween Potatoes - Pinkwater, Daniel Manus; 1941-; Pinkwater, Jill (New York, 1999)
Despite the insistence of her second-grade teacher that their Halloween celebration will focus on pumpkins, Big Gloria finds a way to introduce her favorite vegetable, the potato.
Accelerated Reader AR